Toxicologic evaluation of acute and subacute oral administration of Cucurbita maxima seed extracts to rats and swine - Queiroz-Neto, Antonio de; Mataqueiro, Maria Isabel; Santana, Aureo Evangelista; Alessi, Antonio Carlos (Elsevier, 1994)
The extract prepared from dried seeds of Cucurbita maxima was administered to rats and pigs. Following a single dose or 4 weeks of daily oral administration, the extract produced no changes in serum glucose, urea, creatinine, total protein, uric acid, GOT, GPT, LDH or blood counts. Urine analysis (urea, uric acid, creatinine, total protein, Na and K), as well as histopathological investigation, showed no abnormalities. These results taken as a whole indicate that the seeds of C. maxima as used in Brazilian folk medicine are not toxic for rats and swine.
Keywords: Cucurbita maxima; Pumpkin; Toxicity; alanine aminotransferase; aspartate aminotransferase; creatinine; glucose; lactate dehydrogenase; plant extract; protein; urea; uric acid; aminotransferase blood level; animal experiment; animal tissue; blood cell count; controlled study; creatinine blood level; creatinine urine level; drug safety; female; glucose blood level; lactate dehydrogenase blood level; nonhuman; oral drug administration; potassium urine level; protein urine level; rat; sodium urine level; swine; traditional medicine; urea blood level; uric acid blood level; uric acid urine level; urinalysis; weight gain; Administration, Oral; Animal; Blood Cell Count; Blood Glucose; Blood Proteins; Brazil; Creatinine; Drug Evaluation, Preclinical; Electrolytes; Female; Heart; Kidney; Liver; Lung; Pancreas; Plant Extracts; Random Allocation; Rats; Rats, Wistar; Seeds; Spleen; Support, Non-U.S. Gov't; Swine; Urea; Uric Acid